2012
DOI: 10.1016/j.athoracsur.2011.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Acute Kidney Injury Duration After Cardiac Surgery: An Externally Validated Tool

Abstract: Background Acute kidney injury (AKI) duration following cardiac surgery is associated with poor survival in a dose-dependent manner. However, it is not known what peri-operative risk factors contribute to prolonged AKI and delayed recovery. We sought to identify peri-operative risk factors that predict duration of AKI, a complication that effects short and long term survival. Methods We studied 4,987 consecutive cardiac surgery patients from 2002 through 2007. AKI was defined as a ≥0.3 (mg/dL) or ≥50% increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 21 publications
1
35
0
4
Order By: Relevance
“…However, clinical risk scores for persistent AKI have not been validated for general use and the risk factors that contribute to persistent AKI, AKD, and delayed recovery among hospitalized patients are not known. Several studies have identified clinical risk scores, biomarkers, imaging, and functional tests to differentiate rapid reversal of AKI from persisting AKI [19][20][21][22][23][24][25][26][27] (see Supplementary information S2 (table)). In the opinion of the ADQI workgroup, these tools would likely work well together and are a recommended area of future research…”
Section: Identification Of Persistent Akimentioning
confidence: 99%
“…However, clinical risk scores for persistent AKI have not been validated for general use and the risk factors that contribute to persistent AKI, AKD, and delayed recovery among hospitalized patients are not known. Several studies have identified clinical risk scores, biomarkers, imaging, and functional tests to differentiate rapid reversal of AKI from persisting AKI [19][20][21][22][23][24][25][26][27] (see Supplementary information S2 (table)). In the opinion of the ADQI workgroup, these tools would likely work well together and are a recommended area of future research…”
Section: Identification Of Persistent Akimentioning
confidence: 99%
“…Zidentyfikowano dotąd kilkanaście potencjalnych czynników ryzyka CSA-AKI, do których można zaliczyć obciąże-nia przedoperacyjne (starszy wiek, cukrzycę, nikotynizm oraz podwyższone wyjściowe stężenie kreatyniny), czynniki śródoperacyjne (konieczność zastosowania leków inotrpowych, konieczność przetoczeń preparatów krwi, czas zakleszczenia aorty oraz konieczność ponownego zastosowania krążenia pozaustrojowego), te związane z okresem CPB, cardiopulmonary by-pass (diurezę podczas CPB oraz fakt zastosowania furosemidu podczas CPB) oraz 5 parametrów pooperacyjnych (konieczność transfuzji, użycie diuretyków, leków wazokonstrykcyjnych, inotropowych oraz antyartymicznych) [20,21]. Najnowsza metaanaliza przeprowadzona przez Kumar i wsp.…”
Section: Czynniki Ryzyka Csa-akiunclassified
“…Attribute 2 -Impairment of physiological functions: comprises the domains of physiological functions: impaired elimination, cardiovascular complications, impaired structural integrity (complication related to the surgical wound healing phases), breathing complications, digestive and sexual dysfunction. These domains are manifested by signs and symptoms that have an impact on patients' lives, hindering the recovery to the same condition as in the preoperative period (16)(17)(18) . The impaired structural integrity is an expressive domain in literature.…”
Section: Attributes Of the Delayed Surgical Recovery Conceptmentioning
confidence: 99%